International Perspectives and Initiatives (2015)
This is the 15th in a series of articles exploring international trends in health science librarianship in the 21st century. It is the third of four articles pertaining to different regions in the African continent. The present issue focuses on countries in West Africa (Ghana, Nigeria and Senegal). The next feature column will investigate trends in North Africa.